Diversity of Eimeria Species in Wild Chamois Rupicapra spp.: A Statistical Approach in Morphological Taxonomy - Berrilli, Federica; Montalbano Di Filippo, Margherita; De Liberato, Claudio; Marani, Ilaria; Lanfranchi, Paolo; Ferrari, Nicola; Trogu, Tiziana; Formenti, Nicoletta; Ferretti, Francesco; Rossi, Luca; D'Amelio, Stefano; Giangaspero, Annunziata (Frontiers in Veterinary Science, 2020)
Wildlife is frequently infected by intestinal protozoa, which may threaten their fitness and health. A diverse community of Eimeria species is known to occur in the digestive tract of mountain-dwelling ungulates, including chamois (genus Rupicapra). However, available data on Eimeria diversity in these taxa is at times inconsistent and mostly dated. In the present study, we aimed to revisit the occurrence of Eimeria spp. in the Alpine subspecies of the Northern chamois (Rupicapra rupicapra rupicapra) and the Apennine subspecies of the Southern chamois (Rupicapra pyrenaica ornata) in Italy, using an integrated approach based on a hierarchical cluster analysis (HCPC) applied to oocyst morphology and morphometry. A total of 352 fecal samples were collected from R. r. rupicapra (n = 262) and R. p. ornata (n = 90). Overall, 85.3% (300/352) of the animals tested microscopically positive to Eimeria spp. Based on morphological analysis, we identified all the eimerian species described in chamois. Through the HCPC method, five clusters were generated, corresponding to E. suppereri, E. yakimoffmatschoulskyi, E. riedmuelleri (two different clusters), and E. rupicaprae morphotypes. The well-defined clusters within E. riedmuelleri support the existence of two distinct morphological groups, possibly referable to different taxonomic units. This study suggests that combining a morphometrical approach with a powerful statistical method may be helpful to disentangle uncertainties in the morphology of Eimeria oocysts and to address taxonomic studies of eimeriid protozoa at a specific host taxon level.